Semites and anti-Semites : an inquiry into conflict and prejudice - Bernard Lewis (Weidenfeld and Nicolson, London, 1986)
An analysis of antisemitism since 1945, focusing on the Arab-Israeli conflict and differentiating between political opposition to Israel and antisemitic anti-Zionism. Surveys modern Jewish history, including the origins of the terms "semites" and "antisemites", the rise of Zionism, and the Holocaust. Emphasizes that, before the rise of modern antisemitism, Muslims were not antisemitic but Jews were never accorded full rights and the Muslim stereotype of the Jew was a hostile one. Examines the influence of Nazi ideology on Arab nationalism. Political opposition to Zionism as European colonialism was influenced by antisemitic concepts of a Jewish-Bolshevik (later, American) conspiracy. Since the 1950s, a satanic stereotype of the Jew has become part of the Arab and Islamic world view. "For Christian antisemites, the Palestine problem is a pretext and an outlet for their hatred; for Muslim antisemites, it is the cause". (From the Bibliography of the Vidal Sassoon International Center for the Study of Antisemitism)